Hybrid Lithium‐Ion/Metal Electrodes Enable Long Cycle Stability and High Energy Density of Flexible Batteries. (16th June 2022) - Xie, Chuan; Chang, Jian; Shang, Jian; Wang, Lei; Gao, Yuan; Huang, Qiyao; Zheng, Zijian
Abstract: High‐energy, stable, and flexible lithium batteries are highly demanded for next‐generation flexible and wearable electronics. Although the cycling stability of flexible lithium‐ion batteries (LIBs) is high, their energy density reaches the bottleneck because of the use of graphite anode. On the other hand, flexible lithium‐metal batteries provide higher energy density because of the use of lithium (Li) metal anode, but the cycling stability is poor. Herein, a new type of flexible hybrid lithium‐ion/metal battery (f‐LIMB) is reported, which simultaneously possesses enhanced energy density, stable cycling behavior, and outstanding flexibility. f‐LIMB is enabled by using the prelithiated carbon cloth as the anode, which improves the initial Coulombic efficiency by a prior formation of solid electrolyte interface, benefits the subsequent deposition of Li metal due to the preformed lithiophilic Li x C6 compounds, and enhances the cycle life and energy density of batteries through a Li compensation mechanism. The f‐LIMB full cell possesses an improved gravimetric and volumetric energy density by as much as 64% and 67%, in comparison to the flexible LIB counterpart, and pertains high capacity retention of 84% after 1000 charge/discharge cycles. In addition, the f‐LIMB can be readily bent down to a small radius of 2.5 mm. Abstract : In this work, a facile direct‐contact prelithiation method is used for the fabrication of prelithiated carbon cloth and the as‐fabricated anode enables the assembly of flexible hybrid lithium‐ion/metal batteries, which present high ICE, long cycling stability, enhanced energy density as well as excellent flexibility compared to the conventional lithium‐ion batteries.